Sports dentistry: a perspective for the future - Paulo Vinícius Soares; Andrea Barros Tolentino; Alexandre Coelho Machado; Reinaldo Brito Dias; Neide Pena Coto (Escola de Educação Física e Esporte da Universidade de São Paulo (EEFEUSP), 2014)
Sports Dentistry (SD) acts in the prevention, maintenance and treatment of oral and facial injuries, as well as the collection and dissemination of information on dental trauma, beyond stimulus to research. Establishes as a duty for the dentist detect problems related to the athlete's stomatognathic system. This essay is based on the provided data from the literature related to SD, including definition, practice areas and research fields. To discuss the data, six areas were categorized: shares in sports dentistry; oral health of athlete; sports-related dental implications; dental-facial trauma; face shields; and mouthguards. The analyzed data show that the SD is still an underexplored field of action by dentists, but it is expanding, despite not being recognized specialty by the Federal Council of Dentistry, but the Brazilian Academy of Sports Dentistry has been created with a mission to show the real importance of Dentistry in sport. The dentist should be part of the group of professionals associated with the athlete to perform periodic checks in order to ensure oral health which may contribute to athletes´performance. When impact occurs, however, it would be possible reduce the severity of the impact related to injuries, by using helmets, masks, goggles, face shields and mouthguard. Additionally, it is imperative that dentists, sports coaching, athletes, and professional who work with athletes be aware of the benefits of incorporating SD as an important academic and professional subject.